The incidence of sexual harassment: A preliminary report - Mohamed, Mahmood Nazar; Marican, Sabitha; Jamaluddin, Zakiyah; Ahmad, Rusli (Pusat Penyelidikan dan Perundingan, Universiti Utara Malaysia, 2001)
The study of sexual harassment has not gained its momentum in this country, as most studies are at its preliminary stage.This study also investigates the incidence of sexual harassment but more confined to the northern region of the country. A total of 52 respondents participated by answering the Utara Sexual Harassment Perception Questionnaire (USHPQ) developed by Sabitha (1999) based on indicators used in Soutar (1977), Reese et al., (1997) and Fitzgerald (1991). Four categories of SH were used; visual, verbal, non-verbal, and physical. Respondents views and experiences were grouped into the following categories; acts which are very disturbing, acts which are disturbing and acts which are not considered as sexual disturbing. Differences in perception between men and women were noted and discussed.